Accelerating bone defects healing in calvarial defect model using 3D cultured bone marrow‐derived mesenchymal stem cells on demineralized bone particle scaffold. (27th February 2020) - Kim, Jin Woo; Park, Jong Ho; Muthukumar, Thangavelu; Shin, Eun Yeong; Shin, Myeong Eun; Song, Jeong Eun; Khang, Gilson
Abstract: Bone defects are usually difficult to be regenerated due to pathological states or the size of the injury. Researchers are focusing on tissue engineering approaches in order to drive the regenerative events, using stem cells to regenerate bone. The purpose of this study is to evaluate the osteogenic differentiation of bone marrow‐derived mesenchymal stem cells (BMSCs) on biologically derived Gallus gallus domesticus ‐derived demineralized bone particle (GDD) sponge. The sponges were prepared by freeze‐drying method using 1, 2, and 3 wt% GDD and cross‐linked with glutaraldehyde. The GDD sponge was characterized using scanning electron microscopy, compressive strength, porosity, and Fourier transform infrared. The potential bioactivity of the sponge was evaluated by osteogenic differentiation of BMSCs using 3(4, dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay and quantifying alkaline phosphatase (ALP) activity. in vivo experiments were evaluated through a micro‐computerized tomography (μ‐CT) and histological assays. The analysis confirmed that an increase in the concentration of the GDD in the sponge leads to a higher bone formation and deposition in rat calvarial defects. Histological assay results were in line with μ‐CT. The results reported in this study demonstrated the potential application of GDD sponges as osteoinductor in bone tissue engineering in pathological or nonunion bone defects.